Assessment of workplace hazards among working children in al amen city, Baghdad - Sahb Al Saidi, Ali Abd Ali (AL-Kindy College Medical Journal, 2010)
Back ground: One out of six children in the world today is involved in child labor, doing work that is damaging to his or her mental, physical and emotional development. Objective: Assessment of some health problems among the studied working children. Method; A cross-sectional study was conducted in Al Amen Primary Health Care (PHCC) during the period from January to August 2009, a sample of 6048 children were selected randomly(3218girls and2866 boys age between 5-17 years ) and interviewed to collect information using a structured questionnaire form, information related to different aspects of child labor prevention were included in the form as well as a general medical examination and laboratory assessment. Results:. The frequency of child labor was 10.95% among the children study, and the detection of work related illnesses among working children was observed in 402 working children(60.36%).While work related accidents was 264(39.63%).Both sexes showed difference in frequency of labor (77% boys and 23% girls).there was association between malnutrition and child labor(x2 =64.11 ,df=1,p-value<0.05)also such a association with smoking habit (x2 =98.53,df=1,p-value <0.05) .The highest frequency of child labor (32%)was found among 15-17 years age group of boys. While the highest frequency of child labor (11.71%)was found among 9-11 years age group of girls. Out of 666 working children there are 26 child with lead poisoning(3.90%). Conclusion: Child labor can induce many health problems among the studied working children